Covered distances of handball players obtained by an automatic tracking method - Russomanno, T. G.; Misuta, M. S.; Menezes, R. P.; Brandao, B. C.; Figueroa, P. J.; Leite, N. J.; Goldstein, S. K.; Barros, R. M. L. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The aim of this work is to obtain the distances covered by handball players and their velocities during a match using a new approach based on automatic tracking method described in Figueroa et. al. (2006a, 2006b) and the Adaboost detector (Okuma, 2004). A whole game of a Brazilian regional handball championship for players under age of 21 was recorded. Applying the mentioned automatic tracking, the accumulated covered distances and the velocities were calculated for all the players. The results of average covered distances (±SD) in the 1st and 2 nd halves were 2199(±230) and 2453(±214). The results of covered distances and the velocities allow individual and collective analyses of the players by the team staff. The proposed method revealed to be a powerful tool to improve physical analysis of the handball players.